2021
DOI: 10.1139/cjpp-2021-0108
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase (iNOS) mediates ethanol-induced redox imbalance and upregulation of inflammatory cytokines in the kidney

Abstract: Overexpression of the inducible isoform of the enzyme nitric oxide synthase (iNOS) has been associated to pathological processes in the kidney. Ethanol consumption induces the renal expression of iNOS. However, the contribution of this enzyme to the deleterious effects of ethanol in the kidney remains elusive. We examined whether iNOS plays a role in the renal dysfunction and oxidative stress induced by ethanol consumption. With this purpose, male C57BL/6 wild-type (WT) or iNOS-deficient (iNOS-/-) mice were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Alcohol abuse induces liver inflammation and has been associated with myopathy (49)(50)(51). A recent study by de Silva et al suggested a role of the inducible nitric oxide synthase in ethanol-induced oxidative stress and proinflammatory cytokines production in the kidney (51). These findings could explain our results since alcohol was the main cause of liver disease.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Alcohol abuse induces liver inflammation and has been associated with myopathy (49)(50)(51). A recent study by de Silva et al suggested a role of the inducible nitric oxide synthase in ethanol-induced oxidative stress and proinflammatory cytokines production in the kidney (51). These findings could explain our results since alcohol was the main cause of liver disease.…”
Section: Discussionsupporting
confidence: 57%
“…Alcohol consumption could explain the relationship between sarcopenia and renal impairment in the context of cirrhosis. Alcohol abuse induces liver inflammation and has been associated with myopathy (49)(50)(51). A recent study by de Silva et al suggested a role of the inducible nitric oxide synthase in ethanol-induced oxidative stress and proinflammatory cytokines production in the kidney (51).…”
Section: Discussionmentioning
confidence: 99%
“…NOS2 is an important intracellular messenger and molecular marker in the mechanism of inflammation ( Jiang et al, 2016 ). In the kidney, NO is involved in the regulation of renal vascular resistance, glomerular filtration rate and maintenance of renal structural integrity ( Da Silva et al, 2021 ). Many studies have shown that NOS2 plays a key role in the pathogenesis of metabolic nephropathy, and it has been found in the pathogenesis of chronic nephropathy that elevated NOS2 levels produce highly reactive NO, which is associated with chronic low-grade inflammatory states ( Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic ethanol consumption affects cardiac, hepatic, and urinary systems, as well as food and water intake in humans and rodents [49][50][51][52][53][54] . Therefore, we measured food and water intake, as well as liver, kidney, and heart masses.…”
Section: Discussionmentioning
confidence: 99%